Volume 1: Aircraft Engine; Marine; Turbomachinery; Microturbines and Small Turbomachinery 2000
DOI: 10.1115/2000-gt-0470
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Flow Turbines: Inlet and Exit Flow Under Steady and Pulsating Conditions

Abstract: The performance and detailed flow characteristics of a high pressure ratio mixed flow turbine has been investigated under steady and pulsating flow conditions. The rotor has been designed to have a nominal constant incidence (based on free vortex flow in the volute) and it is for use in an automotive high speed diesel turbocharger. The results indicated a departure from the quasi-steady analysis commonly used in turbocharger turbine design. The pulsations from the engine have been followed through the inlet pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 0 publications
1
24
0
Order By: Relevance
“…The rotational speed of the turbine simulations was 50000 r/min, which was a main operation condition of the turbocharger while the design speed was 70000 r/min. Another reason for choosing this running speed is that it may have more obvious unsteady characteristics in the turbine at a lower running speed [15,16]. The static temperature imposed at the inlet boundary was 873 K. The residuals of steady simulations were less than 10 5 and errors between inlet and outlet mass flow rates were less than 0.1% after 4000 iteration steps, which meant that good convergence was obtained.…”
Section: Resultsmentioning
confidence: 99%
“…The rotational speed of the turbine simulations was 50000 r/min, which was a main operation condition of the turbocharger while the design speed was 70000 r/min. Another reason for choosing this running speed is that it may have more obvious unsteady characteristics in the turbine at a lower running speed [15,16]. The static temperature imposed at the inlet boundary was 873 K. The residuals of steady simulations were less than 10 5 and errors between inlet and outlet mass flow rates were less than 0.1% after 4000 iteration steps, which meant that good convergence was obtained.…”
Section: Resultsmentioning
confidence: 99%
“…It is shown by numerous experimental and computational studies that for comparable time-averaged inlet and exit conditions, the two flows exhibit different time-averaged performance. 6,7,15,16,20,21,26,37,40,41 This deviation from steady behavior is well documented in parametric studies of pulse shape, amplitude, phase, and frequency, upstream geometry, as well as full and partial admission conditions.…”
Section: Introductionmentioning
confidence: 88%
“…Depending on the pulse shape and amplitude, substantial portions of the cycle may be spent at off-design incidence, and rotor designs with poor off-design performance will suffer accordingly. 20,21 During periods of little or no mass flow rate through the rotor, the turbine undergoes a state of "free-wheeling," and experiences what are known as windage losses. Friction between the approximately quiescent flow at the rotor boundaries effectively decelerates the rotor, generating additional losses.…”
Section: Figure 4 Variation Of Incidence Over a Pulse Cycle 20mentioning
confidence: 99%
“…They indicated that the method leads to more accurate prediction and proved it by extensive validation procedure with the work of Karamanis [3]. Palfreyman and Martniez-Botas indicated that the flow field in the turbine passage under pulsating flow condition is highly disturbed.…”
Section: Introductionmentioning
confidence: 94%